2020
DOI: 10.3892/etm.2020.8690
|View full text |Cite
|
Sign up to set email alerts
|

A mid‑pregnancy risk prediction model for gestational diabetes mellitus based on the maternal status in combination with ultrasound and serological findings

Abstract: to their diagnostic results at 24-28 weeks of pregnancy. Univariate analysis was performed to investigate the significance of the maternal clinical parameters for GDM diagnosis and a GDM prediction model was established using stepwise regression analysis. The predictive value of the model was evaluated using a Homer-Lemeshow goodness-of-fit test and a receiver operating characteristic curve (ROC). The model demonstrated that age, pre-pregnancy body mass index, a family history of diabetes mellitus, polycystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In this study, 19 prediction models were established using the LR models [ 17 , 18 , 20 - 23 , 26 - 33 , 35 - 39 ], and the overall pooled AUROC for the LR models for predicting GDM was 0.8151 ( Figure 5 ). The overall pooled AUROC for non-LR models to predict GDM was 0.8891 ( Figure 6 ), the highest value among these subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 19 prediction models were established using the LR models [ 17 , 18 , 20 - 23 , 26 - 33 , 35 - 39 ], and the overall pooled AUROC for the LR models for predicting GDM was 0.8151 ( Figure 5 ). The overall pooled AUROC for non-LR models to predict GDM was 0.8891 ( Figure 6 ), the highest value among these subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy was employed to ensure the model could be used in situations where laboratory measurements were not readily available. We selected nine variables for GDM prediction after reviewing 28 published studies that reported findings from cohort and case–control studies, diagnosis or assessments of GDM, or development of predictive or risk models 27 30 , 58 81 (listed and summarized in Table S1 and Figure S1 ) and in accordance with the information available for the CME study. The selected variables included maternal age (years); family history of type 2 diabetes (yes/no); previous diagnosis of hypertension (yes/no); BMI (kg/m 2 ); gestational week at first prenatal visit; parity (number); birth weight of last child (grams); type of capillary glucose measurement at first prenatal visit (random/fasting); and capillary blood glucose level at first prenatal visit (mg/dL).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, GD predictive models have been established to identify pregnant women at high risk and to provide a scientific basis for the early detection of high‐risk GD pregnancies 29,30 . However, obtaining clinical biochemical indicators or the imaging data of pregnant women for use in prediction models is challenging, thus reducing each model's applicability.…”
Section: Introductionmentioning
confidence: 99%